Single center experience with the Potts shunt in severe pulmonary arterial hypertension. (March 2018) - Kirkpatrick, Edward C.; Handler, Stephanie S.; Foerster, Susan; Gudausky, Todd; Tillman, Katy; Mitchell, Michael
Abstract: Background: There remains limited options for end stage pulmonary arterial hypertension that is refractory to medical therapy. The reprisal of the Potts shunt (pulmonary artery to descending aorta anastomosis) has been used to decrease right ventricle (RV) afterload by creating a right to left shunt in effort to promote lung transplant free survival. Methods: Retrospective review of three patients ages 16, 19, and 27 years old who underwent the creation of a "reverse" Potts shunt at our institution in 2016. Results: The patients were WHO functional class III or IV and on three classes of pulmonary hypertension specific drug therapy including IV prostacyclin. All patients had RV dysfunction and suprasystemic RV pressures. Two patients had a catheterization for dilation and stenting of a tiny patent ductus arteriosus (PDA) and one had emergent surgical placement of a pulmonary artery to descending aorta conduit. The catheterization procedures were well tolerated without complications. The surgical procedure was complicated with heavy bleeding and respiratory failure. All patients recovered from their procedure and experienced improved functional class with decrease in RV pressures to systemic levels but no improvement in RV function. One catheterization patient required restenting due to stent fracture at 7 months. Our surgical patient died from massive hemoptysis 13 months after the procedure. Conclusions: Reverse Potts shunt physiology may be an option for end-stage PAH patients with suprasystemic RV pressures. Optimal timing of this procedure remains unclear, but if feasible, PDA stenting, even in adult patients may be accomplished with low morbidity. Highlights: Potts shunt can be used to improve functional patients with medically refractory pulmonary arterial hypertension. PDA stenting can be done with low risk in even in adult patients with severe pulmonary arterial hypertension. Long standing right ventricular dysfunction may not improve despite reduction of right ventricular afterload.